Analysis of the relationship between physical activity, well-being and hypercapnic tolerance among students of different fields of study - Anna Ostrowska; Hubert Pepłowski (Polish Journal of Sports Medicine, 2026)
Background. Physical activity supports well-being, mental health and quality of life. Breathing pattern and tolerance of respiratory sensations may also be associated with stress, sleep and psychophysical functioning. The control pause (CP) is a non-maximal breath-hold after normal exhalation, ending at the first clear urge to breathe. The study assessed associations between physical activity, WHO-5 well-being and CP in students of different fields of study.Material and methods. The cross-sectional survey enrolled 73 students; complete data from 63 participants (mean age 22.97 years) were included in the analysis. Physical activity and lifestyle were assessed using an original questionnaire, mental well-being using the WHO-5, and breathing-related tolerance using a self-performed CP measurement. Pearson’s chi-square test, Cramér’s V and Spearman’s rank correlation were used (p<0.05).Results. The mean WHO-5 score was 13.37/25 (53.46/100). Physical activity was moderate in 38.1% and high or very high in 36.5%; 58.7% reported at least 30 minutes of activity on three or more days per week. Poor or very poor sleep was reported by 27.0%, and 49.2% experienced tension or stress on 6–14 of the previous 14 days. The mean CP was 23.6411.30 s; 38.1% obtained ≤19 s, 33.3% 20–29 s and 28.6% ≥30 s. Physical activity was associated with well-being (χ=33.14; p=0.007; V=0.36; ρ=0.62; p<0.001). CP correlated with WHO-5 scores (ρ=0.46; p<0.001), stress (ρ=-0.39; p=0.002) and sleep quality (ρ=0.34; p=0.006), and differed according to activity level and frequency.Conclusions. Higher physical activity co-occurred with better well-being and longer CP. CP may serve as an educational and preventive-health tool by supporting simple self-observation and self-monitoring of breathing, but it does not replace spirometry, capnography or clinical diagnosis.